Some conceptual and grammatical properties of body part metonymies in English and Bosnian - Imamović Adisa; Ibrišimović Anela Mulahmetović (ExELL (Explorations in English Language and Linguistics))
The paper deals with metonymies having body parts as source domains in English and Bosnian. According to Cognitive Linguistics standpoint, human cognition is based on bodily functioning. Therefore, we started from the hypothesis that most body part metonymies are very similar across languages and cultures, and share similar properties. The aim of the paper was threefold: first, to examine whether metonymies with body parts as source domains have common grammatical and conceptual properties in English, secondly to examine whether they share the same properties in Bosnian, and thirdly to compare the two languages in this respect. We analysed body part metonymies in terms of some grammatical properties such as the use of singular and plural, specific and generic reference, grammatical recategorisation from count to mass nouns, noun-to-verb conversion, and some conceptual properties such as source-in-target vs. target-in-source metonymies, metonymic chains and combination of metaphor and metonymy. Many common features were found both within the respective languages under consideration and in cross-linguistic analysis. The minor differences found in contrasting the data from the two languages are mainly the result of differences in grammatical systems.